2020
DOI: 10.1016/j.carbon.2019.12.092
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-polyelectrolyte multilayer membranes with tunable structure and internal charge

Abstract: One great advantage of graphene-polyelectrolyte multilayer (GPM) membranes is their tunable structure and internal charge for improved separation performance. In this study, we synthesized GO-dominant GPM membrane with internal negatively-charged domains, polyethyleneimine (PEI)-dominant GPM membrane with internal positively-charged domains and charged-balanced dense/loose GPM membranes by simply adjusting the ionic strength and pH of the GO and PEI solutions used in layer-by-layer membrane synthesis. A combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Comparisons of (a) Na 2 SO 4 and (b) MgSO 4 separation performances of various LBL-based NF membranes in the literature. (PEI 1.5 /GO 0.3 /PEI 3.0 )/hPAN from ref , (PDDA/GO) 4.0 from ref , PS/PDA/CS/SiO 2 from ref , (CS/PAA) 4 and (CS/PAA) 4 CS from ref , LBL-cPP and LBL-cPP from ref , and (PEI/GO) 3 from ref . PEI, polyethylenimine; GO, graphene oxide; PDDA, poly­(diallyldimethyl ammonium chloride); PS, polysulfone; PDA, polydopamine; CS, chitosan; PAA, poly­(acrylic acid); hPAN, hydrolyzed PAN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of (a) Na 2 SO 4 and (b) MgSO 4 separation performances of various LBL-based NF membranes in the literature. (PEI 1.5 /GO 0.3 /PEI 3.0 )/hPAN from ref , (PDDA/GO) 4.0 from ref , PS/PDA/CS/SiO 2 from ref , (CS/PAA) 4 and (CS/PAA) 4 CS from ref , LBL-cPP and LBL-cPP from ref , and (PEI/GO) 3 from ref . PEI, polyethylenimine; GO, graphene oxide; PDDA, poly­(diallyldimethyl ammonium chloride); PS, polysulfone; PDA, polydopamine; CS, chitosan; PAA, poly­(acrylic acid); hPAN, hydrolyzed PAN.…”
Section: Resultsmentioning
confidence: 99%
“…9−12 Recently, layer-by-layer (LBL) assembly has gained immense popularity for fabricating high-performance NF membranes because it is facile, scalable, cost-effective, and environmentally friendly. 13 By alternative adsorption of two polyelectrolytes with opposite charge properties onto porous substrates, high-performance NF membranes with a flexible charged selective layer, desired water permeability, and satisfied salt rejection have been successfully developed. 14−16 For example, Liu et al developed a hollow fiber NF membrane based on LBL depositions of poly(allylamine hydrochloride) (PAH) and poly(sodium 4-styrenesulfonate) (PSS) followed by glutaraldehyde (GA) cross-linking.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Crosslinking between GO layers is the most commonly used method to fabricate GO membranes with uniform channel size because of the swelling behavior of these membranes in water being suppressed [14,17–25] . Up to now, this kind of method is easy to implement via intercalating some cross‐linkers with diameter around 1 nm such as covalent bonding agents, [17–22] inorganic salt ions, [23–24] planar cations [14] and polycations [25] . Among them, covalent bonding agents have the advantages of high stability and controllable cross‐linking size.…”
Section: Introductionmentioning
confidence: 99%
“…The irreversible LbL deposition of polyelectrolytes is mainly driven by electrostatic attractions between the oppositely charged polyelectrolytes. With this approach, the LNF membranes are commonly fabricated using at least one weak polyelectrolyte (e.g., one strong and one weak polyelectrolyte or two weak polyelectrolytes), ,, whereas DNF membranes are typically fabricated using two strong polyelectrolytes. Several critical membrane properties, such as the pore size distribution, surface charge, and active layer thickness, are affected by multiple factors in the LbL deposition process, such as the type of polyelectrolytes, , polyelectrolyte concentration, ionic strength of the polyelectrolyte solution, pH, and temperature. , Adjusting these parameters provides avenues to control the membrane permeance and ion selectivity. Beyond these parameters, integrating various types of additives (e.g., nanomaterials) into the PEM is also a widely explored approach to enhance the permselectivity. , …”
Section: Introductionmentioning
confidence: 99%
“…Beyond these parameters, integrating various types of additives (e.g., nanomaterials) into the PEM is also a widely explored approach to enhance the permselectivity. 49,50 In our recent studies, we reported a novel and cost-effective approach to dramatically enhance the permeance of loose NF membranes for removing macromolecules (e.g., humic acid and dyes). 16,32 This approach is based on the intercalation of surfactant bilayers between weak polycations (polyethylenimine, PEI) and strong polyanions (polystyrene sulfonate, PSS) and has been demonstrated to be capable of enhancing the performance by multiple folds without compromising the rejection of macromolecules.…”
Section: ■ Introductionmentioning
confidence: 99%